Identification of a Secreted Cholesterol-Dependent Cytolysin (Mitilysin) from Streptococcus mitis - Jefferies, Johanna (American Society for Microbiology, 2007)
We have detected a cholesterol-dependent cytolysin, which we have named mitilysin, in a small number of Streptococcus mitis isolates. We have sequenced the mitilysin gene from seven isolates of S. mitis. Comparisons with the pneumococcal pneumolysin gene show 15 amino acid substitutions. S. mitis appear to release mitilysin extracellularly. Certain alleles of mitilysin are not recognized by a monoclonal antibody raised to the related toxin pneumolysin. Based on enzyme-linked immunosorbent assay and neutralization assay results, one isolate of S. mitis may produce a further hemolytic toxin in addition to mitilysin. As genetic exchange is known to occur between S. mitis and Streptococcus pneumoniae, this finding may have implications for the development of vaccines or therapies for pneumococcal disease that are based on pneumolysin.